ECB macroeconometric models for forecasting and policy analysis: Development, current practices and prospective challenges - Matteo Ciccarelli; Matthieu Darracq Pariès; Romanos Priftis (European Central Bank (ECB), 2024)
This paper takes stock of the ECB's macroeconometric modelling strategy by focusing on the models and applications used in the Forecasting and Policy Modelling Division. We focus on the guiding principles underpinning the current portfolio of the main macroeconomic models and illustrate how they can in principle be used for economic forecasting, scenario and risk analyses. We also discuss the modelling agenda which is currently under development, focusing notably on heterogeneity, machine learning, expectation formation and climate change. The paper makes it clear that the large macroeconometric models typically developed in central banks remain stylised descriptions of our modern economies and can fail to predict or assess the nature of economic events (especially when big crises arise). But even in highly uncertain economic conditions, they can still provide a meaningful contribution to policy preparation. We conclude the paper with a roadmap which will allow the ECB and the Eurosystem to exploit technological advances and cooperation across institutions as a useful means of ensuring that the modelling framework is not only resilient to disruptive events but also innovative.
Keywords: C30; C53; C54; E52; 330; Economic models; monetary policy; forecasting; macroeconometrics